Pengaruh Jarak Tanam terhadap Produksi Tiga Sayuran Indigenous - Faiqotul Himma; Bambang Sapta Purwoko (Jurnal Hortikultura Indonesia, 2013)
ABSTRACTThe purpose this research was to determine the effects of plant spacing (population) on growth and yield of  three  indigenous  vegetables  (kemangi, kenikir,  and  katuk).  The  research  was  conducted  at Cikabayan experimental  farm  in  Darmaga,  Bogor  from  April  until November  2010.  The  experiment  design  was  a Randomized  Complete Block  Design  one  factor  with  four  treatments  of  plant  spacing  or population: 25  cm  ×  13. 33  cm  (population  300  000  plants  ha- 1),  25 cm  ×  16  cm  (population  250  000  plants  ha-1), 25 cm × 20 cm (population  200  000 plants  ha- 1), and  25 cm × 26.67 cm (population 150  000 plants  ha- 1), with three replications. Observations included plant height, number of leaves, number of branches, weight yields  per plant and weight yield  per plot. The experiment showed that plant spacing of kemangi did not influence vegetative growth, weight yields  per plant and weight yield  per plot. Plant spacing of kenikir influenced number of leaves, number of branches, weigth yields  per plant.   Plant spacing of katuk did not influence  vegetative growth,  weight yields  per plant and weight yield  per plot.Key words: katuk,   kemangi, kenikir, population, vegetative growth,  yieldABSTRAKPenelitian ini bertujuan untuk melihat pengaruh jarak tanam dalam populasi terhadap pertumbuhan dan hasil dari tiga sayuran indigenous (kemangi, kenikir, dan katuk). Penelitian dilaksanakan di Kebun Percobaan Cikabayan, Darmaga Bogor dari April hingga November 2010. Penelitian menggunakan Rancangan Kelompok Lengkap Teracak satu faktor dengan empat perlakuan jarak tanam: 25 cm × 13:33 cm (populasi 300 000 tanamanha-1),  25 cm × 16 cm (populasi 250  000 tanaman  ha-1),  25 cm × 20 cm (populasi 200  000 tanaman  ha-1), dan 25 cm × 26.67 cm (population 150 000 tanaman ha-1), dengan tiga ulangan. Pengamatan meliputi  tinggi tanaman, jum lah daun, jumlah cabang, bobot hasil per plot. Jarak tanam kenikir berpengaruh terhadap jumlah daun, jumlah cabang, hasil per tanaman . Jarak tanam tidak berpengaruh terhadap pertumbuhan vegetatif , hasil  per tanaman dan hasil  per plot kemangi dan katuk.Kata kunci: katuk, kemangi, kenikir, populasi, pertumbuhan vegetatif, hasi